Geometric Design and Kinematics Analysis of Non-Circular Planetary Gear Train with Cycloid Profile - Nguyen, Hoang Viet; Nguyen, Hong Thai (JST: Engineering And Technology For Sustainable Development, 2021)
This research presents a method to design a non-circular planetary gear. Therein the satellite gear block consists of eccentric cycloidal gear and elliptical cycloidal gear, which have been given. The mathematical equations of two ring non-circular gears are set up according to the gearing theory considering the undercutting conditions. A numerical calculation program was written on Matlab software to calculate and dynamically analyze this planetary gear. The examples presented in the paper shed light on the design steps of the method. The simulation results show that the non-circular cycloidal gear that can overcome the irregular tooth phenomenon on the traditional non-circular involute gear, and when it is necessary to design infinitely variable speed converters with for large amplitudes, the coefficient λ should be adjusted rather than the coefficient µ.